Presupuesto asignado a la Contraloría General de la República y el índice de percepción de la corrupción del Perú 2012-2021 - Rengifo López, Oscar Raul (2024)
This thesis accosts a serious structural problem that is linked to the management of public resources. Thus, we sought to identify the relationship between the budget assigned to the Contraloria Office of total public funds, and the corruption perception index, whose purpose is to evaluate the levels of corruption perceived in the public sector of each country, based in opinions of experts and businessmen. To this end, the statistical records for the period 2012-2021 on the percentage of the budget assigned to the Contraloria Office with respect to the total public budget and the corruption perception index published each year by Transparency International were considered as the study population. After applying the Pearson correlation coefficient for parametric data, it was determined that there is a strong positive relationship between the variables of 79.22%. This means that when the percentage of the budget allocated to the Contraloria Office increases with respect to total public funds, it is expected that the corruption perception index in Peru will also grow.